PELATIHAN PEMBUATAN MEDIA INTERAKTIF BERBANTUAN ISPRING BAGI GURU SEKOLAH MENENGAH PERTAMA DALAM MENDUKUNG KEGIATAN PEMBELAJARAN DI SMP YAPIS MERAUKE - Khumaeroh Dwi Nur'aini; Dessy Rizki Suryani; Irmawaty Natsir (LPPM Universitas Bina Bangsa, 2022)
Learning media is currently an integral part that cannot be separated from the entire learning system. With the use of media the learning process will be more meaningful. One application that can be used in making interactive media is Ispring. Ispring is an application that can convert presentation files into flash format and SCORM/AICC form, which are forms that are often used in LMS (Learning management System) e-learning. Ispring is very easy to use and can be integrated into MS Power Point. The Ispring application provides features that can develop teaching materials in power point format into multimedia in html5 or exe format which can be equipped with music, voice recordings of presenters, videos, and quiz makers. This activity aims to train teachers' abilities and skills in creating interactive media that are designed using applications. Interactive media creation training will be held at Yapis Merauke Middle School. The training activities will begin with an explanation of interactive media and the elements that must be contained in an interactive media, questions and answers during presentations, demonstrations by presenters related to the introduction of the Ispring application, then proceed with the practice of making interactive media using the Ispring application. With this training activity, teachers at Yapis Middle School have become more skilled in creating interactive media using the Ispring application to support an effective and interesting learning process